Hypermethylation of DcR1 Gene-based Biomarker in Non-invasive Cancer Screening of Vietnamese Cervical Cancer Patients - Phuong Kim TRUONG; Thuan Duc LAO; Thuy Ai Huyen LE (Tehran University of Medical Sciences, 2018)
Background: The infection of human papillomavirus (HPV) has been considered as the common cause of cervical cancer, which is the leading cause of cancer death in women, in Vietnam. Recently, hypermethylation at tumor suppressor genes (TSGs) has been also demonstrated to be an early epigenetic event and cofactor in human cancer, including cancer of cervix. This study evaluated the frequency of DcR1 gene promoter hypermethylation status as well as whether did or not an association between patterns of DNA hypermethylation and high-risk HPV infection, led to risk of cervical cancer. Methods: Methylation-Specific-PCR (MSP) was performed to analyze hypermethylation status from 109 liquid-based Papanicolaou test samples, archived and admitted from the Medic Medical Center and Au Lac Clinic Laboratory, Vietnam, from 2011-2014, a kind of non-invasive samples identified whether HPV/or non-HPV, high-risk/low-risk HPV infection. Results: DcR1 promoter was differentially methylated in 50% cases of high-risk HPV genotype 16 and 18 infected samples. In contrast, a low frequency of hypermethylated DcR1 promoter was found in low risk HPV genotype infected sample (16.0%), and non-HPV infected sample (14.6%). A trend toward positive association was found between hypermethylation of DcR1 gene and HPV exposure was observed (P=0.0005). Moreover, the odds ratio (OR) and relative risk (RR) were found in statistical significant value (OR=5.63 (95%CI = 2.25 - 14.07, P<0.01), RR=3.31 (95%CI = 1.75 - 6.26, P<0.01)). Conclusion: The hypermethylation of DcR1 gene promoter is a significant characteristic of high-risk HPV infected samples in Vietnamese cervical patients. The OR and RR values showed that the strong correlation between DcR1 hypermethylation and high-risk HPV infection, in which increased the risk of cervical cancer. The combination of DcR1 hypermethylation and HPV detection based biomarker could be used in non-invasive samples obtained from high-risk cancer patients, offer significant practical advantages.